Spatiotemporal variation of snowpack depths in Northeast China and its mechanisms from 2025 to 2099 based on CMIP6 models - Cheng Xiyao; Zhang Wenshuai; Zhang Dongyou; Zhang Lijuan; Ma Yuyan; Huang Yutao; Zhao Yufeng; Wang Jiaxin; Wang Jinxia; Sun Li (Scientific Reports)
Abstract The temperature rises in Northeast China are anticipated to be among the highest in the world. Investigating the variation in snowpack depth and its characteristics in this region is vital and representative. This study selects the optimal model ensemble using methods such as the Taylor diagram and skill score based on data from CMIP6 models. Statistical methods, including trend and variance analyses, are applied to analyze the spatiotemporal variation of winter snowpack depth in Northeast China from 2025 to 2099 under the SSP1-2.6 (low emission), SSP2-4.5 (moderate emission), and SSP5-8.5 (high emission) scenarios, with possible mechanisms behind these changes. Results indicated that snowpack depth in Northeast China shows no considerable change under SSP1-2.6 and SSP2-4.5, whereas it reduces significantly by 15% under SSP5-8.5. Spatially, the area experiencing a decrease in snowpack depth is roughly 2 to 3 times larger than the area with an increase, compared to the base period. The areas with significant declines in snowpack depth account for 5.6%, 0.9%, and 60.5% under SSP1-2.6, SSP2-4.5, and SSP5-8.5, respectively. The most affected area is located southeast of the study area, where a decrease of 6.98 cm is projected by the end of the 21st century. The geopotential height anomaly (low in the west and high in the east) formed at 500 hPa in Northeast Asia, and the future increase in water vapor will contribute to an increase in winter snowfall in this region. However, the rise in temperature will result in a decrease in snowfall. In addition, snowpack depths in the study area under SSP1-2.6 and SSP2-4.5 are nearly identical but differ considerably from those under SSP5-8.5. As emissions rise, snowpack depth reduces, indicating that snowpack depth is negatively related to temperature. Considerable changes in snowpack depth are observed when the temperature rises to a certain threshold.